DERAJAT BAHAYA PENGGUNAAN AIR ABU, BORAKS DAN FORMALIN PADA KULINER MIE ACEH YANG BEREDAR DI KOTA X PROVINSI ACEH TERHADAP MANUSIA - - Yulizar; Ietje Wintarsih; Achmad Arif Amin (Graduate School Bogor Agricultural University (SPs IPB), 2014)
Mie Aceh is the noodle that formulated with special spices and raw materials wet noodle. Mie Aceh greatly favored by the Aceh’s peoples. This research is conducted by using analysis of titrimetri, photometri and qualitative. The issue of using ash water, borax and formaldehyde of Mie Aceh which circulate at X’s City in Aceh province been examined. After interview with 10 respondents noodle manufacture in X’s City, there were three factors were identified that make them use “air abu” and formaldehyde. The three factors were economics factor, knowledge factor and the dough needs factor. Laboratory analysis was done to see the content of ash water, borax and formaldehyde in Mie Aceh. Theresults of the 25 samples (100%) containing ash water with sodium carbonate test indicators ranges from 0.22% b/b - 0.27 %b/b, borax test results of 25 samples of noodles (100%) showed a negative result. Formalin test on 25 samples showed that positive test results (100%) of formaldehyde content of each sample was >4 mg/L. The results show that Mie Aceh circulating in X’s City was less safe for consumption and dangerous for public health.Keywords : Ash water, borax, formalin, mie Aceh, wet noodles